Penyimpanan Sertifikat Hak Atas Tanah Oleh Notaris Pada Proses Pengikatan Jual Beli (PJB) (Analisis Putusan Nomor 53/Pid.B/2017/Pn.Bkt) - Dila Andika Azhar (Faculty of Law, Andalas University, 2018)
Land purchase agreement is a preliminary agreement made by the parties before a notary create deed of sale before. In case of breach of contract, the notary is often reported to the police on charges of embezzlement due to keeping land rights certificates, even though the parties have signed agreement to authorize the notary public to keep he certificate. Such a problem in fact has also been tried in court. In decision Number 53 / Pid.B / 2017 / PN.Bkt. Elfita Achtar, a notary has been charge due to embezzlement of 4 (four) Right to Build (HGB) certificates owned by PT. Rahman Tamin. The article tries to discuss the case. The research concludes that the Notary Acts does not regulate about the keeping of land certificates in the process of the sale and purchase agreement. However notary deed on the right to keep the certificate has ensured legal certainty to the authority of notary to keep certificate. The consideration in the ruling, pursuant to Article 16 paragraph (1) sub-paragraph a of Notary Law